UNKNOWN TIMOTEY BORDULYAK Bordulyak T. G. Unknown works / od. T.V. Bordulyak; sciences. red., entry. item and comment M.Y.Shalata. – Lviv: PAIS, 2010. – 428 s.: il. - Gorbolis, L. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
A review is devoted to the analysis of the chosen unknown works of the Ukrainian writer Timotey Bordulyak (1863-1936), that a world was recently seen in the Lvov publishing house «PAIS». Pointed on a role and place of prosiest in the all Ukrainian literary and national-cultural process of end ХІХ – beginning of ХХ age.